KOMUNITAS MAMALIA KECIL DI BERBAGAI HABITAT PADA JALUR APUY DAN LINGGARJATI TAMAN NASIONAL GUNUNG CIREMAI - Maharadatunkamsi, Maharadatunkamsi; Maryati, Maryati (JURNAL BIOLOGI INDONESIA, 2008)
ABSTRACTSmall mammal community in various habitats at Apuy track and Linggarjati trackof Gunung Ciremai National Park. Distribution of small mammals at Apuy track(west slope) and Linggarjati track (east slope) of Gunung Ciremai National Park arecorrelated with their habitats. Traps, mist nets and observational methods were conductedto record small mammals from seven different habitats. To interpret such patterns, weconducted cluster analysis based on Jaccard index of similarity resulting five distinctgroups. Species diversity for each habitat differs significantly indicating great diversitydifferences between habitats. Common species appear to occupy disturbed area alongthe habitats examined, where as rare species tend to associate with more distinctivehabitat types. The results seem to suggest that forest may still consitute an substantialcomponent for the preservation of small mammals.Key words: ciremai, small mammals, habitat, distribution, zoning.